From International Economic Relations to International Finance and Business: Research Directions at the Institute of International Economics - Sajnóg, Artur; Miziołek, Tomasz; Motowidlak, Tomasz (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and current development of the Institute of International Economics at the Faculty of Economics and Sociology, University of Łódź. The authors discuss the institute’s scientific and teaching traditions, focusing on the last decade.